ARTIFICIAL INTELLIGENCE (AI) IN ISLAMIC FINANCE: A MAQASID AL-SHARIAH PERSPECTIVE - Nabilah Wafa’ Mohd Najib; Siti Khalilah Basarud-din; Farahdina Fazial, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The integration of Artificial Intelligence (AI) in Islamic finance presents both opportunities and challenges, particularly in ensuring compliance with Maqasid al-Shariah. This paper provides a conceptual analysis of how AI-driven financial services align with the five key dimensions of Maqasid al-Shariah-preservation of religion, life, intellect, wealth, and lineage. While AI enhances efficiency, financial inclusion, and risk management in Islamic finance, ethical concerns arise regarding algorithmic transparency, fairness, data privacy, and the potential for gharar (excessive uncertainty) and riba (usury). This paper explores the necessity of developing AI governance frameworks rooted in Shariah principles to ensure that technological advancements contribute to justice, social welfare, and economic stability in the Islamic finance industry. The study concludes that a Maqasid-based approach to AI in Islamic finance is crucial for maintaining ethical integrity, fostering innovation, and ensuring sustainable financial growth.